Characterization of Ca-Alginate-Gelatin Waste Beads - Salistya, Sarahita Dinda; Ellya Indahyanti; Diah Mardiana; Zubaidah Ningsih (The Journal of Pure and Applied Chemistry Research, 2025)
The rapid growth of industry in Indonesia is partly driven by the emergence of new sectors such as the pharmaceutical industry. This sector has experienced a surge in the production of various types of medical capsules, with shells made from gelatin, colorants, and other components. As capsule production increases, so does the amount of gelatin waste was generated. In this study, beads were manufactured using an extrusion technique with 0.1 M CaCl2 to induce cross-linking. The ratio of alginate to gelatin waste was varied to determine the stability of the beads. The stability of the beads was observed over seven days, and the optimal composition was found to be 1:1. From the results of the TGA/DTA characterization, thermal analysis revealed that the combination of gelatin waste and sodium alginate improved its material properties. SEM results show that the Ca-Alginate-Gelatin waste beads contained alginate network, resulting in a porous structure and amorphous shape. Based on these finding, the beads produced have the potential to serve as adsorbents for use in slowed release fertilizers.